The effect of carbohydrate mouth rinsing on multiple choice reaction time during amateur boxing - Peart, D. J.; Graham, M.; Blades, C.; Walshe, I. H. (International Journal of Sports Physiology and Performance, 2020)
Purpose: To examine whether the use of a carbohydrate mouth rinse (CMR) can improve multiple choice reaction time in amateur boxers during sparring. Methods: A total of 8 male amateur boxers (age 22 [3] y, stature 1.78 [0.07] m, mass 73.6 [14.2] kg) with at least 18 months of experience in the sport volunteered to participate in the study. All participants attended a familiarization session, followed by an experimental (CMR; 6% dextrose) and placebo trials in a randomized order. Participants undertook 3×2 minutes of sparring against an ability- and size-matched (stature and mass) opponent. Multiple choice reaction time and perceived exertion were measured before round 1 and then after each round. The respective mouth rinse was administered in a 25-mL solution for 10 seconds before each round. Magnitude-based inferences were used to compare the results of each round (mean difference; ±90% confidence limits). Results: The CMR was unlikely to have a beneficial effect on multiple choice reaction time compared with placebo (mean±90% confidence limits: 5±9.5, 4±3.4, -1±8.5 lights for rounds 1 to 3, respectively) and had a possibly harmful effect on perceived exertion in round 1 (10±20). There was an unlikely harmful effect on perceived exertion in rounds 2 (1±12) and 3 (9±23). Conclusion: There is no evidence to support the use of CMR during sparring in amateur boxers.